Termična analiza tankih plasti - Cerc Korošec, Romana (Vakuumist, 2003)
The magnitude of the optical modulation of nickel oxide thin films after the colouring/bleaching process depends strongly on the degree of thermal treatment of these films. When they are insufficiently heat-treated, they soon lose their ability to bleach to the initial value. On the other hand, their optical modulation is poor, when they are exposed to too high temperature. This behaviour therefore makes it essential to search for the optimal temperature and duration of heat treatment. The optimization of the electrochromic response of nickel oxide thin films, prepared from NiSOsub4 precursor via the sol-gel route is described in this article, using thermogravimetric analysis. The temperature of heat treatment was chosen from dynamic TG measurements, and the duration of heat-treatment form isothermal ones. The described procedure enables the prepartation of thin films thermally treated to a different extent where the ratio between the thermally indecomposed amorphous phase and nanocrystalline nickel oxide, which is formed during the heat treatment, is varied. The electrochromic response of these films should be determined using additional spectroelectrochemical measurements.
Keywords: diferenčna dinamična kalorimetrija; kalorimetrija; tanke plasti; termična analiza; termogravimetrija